Analyze the quality of Tin-Aluminium binary alloy products concerning of its flowability, tensile strength, and hardness using various types of moulds - Ahmad Zahrul Husaini, Ahmad Helmy (Universiti Malaysia Perlis, 2008)
Tin-aluminium binary alloy is a type of alloy that improve the strength properties of tin. As we know, tin is a type of metal that randomly used in constructive application. So, combined with aluminium, a new type of alloy produced thus can be used in that sector. However, the selection of type of moulding is important in order to produce a high quality products besides giving us a good economic value. Types of moulding process being used in this study are CO2 moulding process, Green sand moulding process and river sand moulding process. These three moulding processes may have similar mixing and making method but vary in materials used. Besides, the flowability test is applied on each of these moulding process to ensure whether it is suitable for precision casting process.